2009
DOI: 10.1213/ane.0b013e3181b2ef75
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Anesthesia-Related Complications in Labor and Delivery, New York State, 2002-2005

Abstract: BACKGROUND Epidemiologic data on anesthesia-related complications occurring during labor and delivery are essential for measuring and evaluating the safety and quality of obstetric anesthesia care but are lacking. We aimed to fill this research gap by exploring the epidemiologic patterns and risk factors of anesthesia-related complications in a large sample of women giving birth in New York hospitals. METHODS Using the Healthcare Cost and Utilization Project State Inpatient Databases files, we identified all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…We identified maternal morbidity using International Classification of Diseases, 9 th Revision (ICD-9-CM) diagnosis and procedure codes[7,8,16-20] supplemented with birth certificate data. [21] (Supplementary Digital Content S1) After determining crude rates of morbidities for each year we classified women as having “pelvic floor morbidity,” “non-pelvic floor morbidity,” and “severe morbidity.” Mothers were considered positive for “pelvic floor morbidity” if they had ICD-9 codes for episiotomy, 3 rd or 4 th degree laceration, vulvar or perineal hematoma or other trauma; or indication of 3 rd or 4 th degree laceration on the birth certificate.…”
Section: Methodsmentioning
confidence: 99%
“…We identified maternal morbidity using International Classification of Diseases, 9 th Revision (ICD-9-CM) diagnosis and procedure codes[7,8,16-20] supplemented with birth certificate data. [21] (Supplementary Digital Content S1) After determining crude rates of morbidities for each year we classified women as having “pelvic floor morbidity,” “non-pelvic floor morbidity,” and “severe morbidity.” Mothers were considered positive for “pelvic floor morbidity” if they had ICD-9 codes for episiotomy, 3 rd or 4 th degree laceration, vulvar or perineal hematoma or other trauma; or indication of 3 rd or 4 th degree laceration on the birth certificate.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of coding accuracy for the types of outcomes reported here suggest that any systematic bias present would be toward under-reporting, rather than over-reporting, of morbidity. 40-42 While there are limitations to restricting our analysis to one state and limitations to what variables can be analyzed using administrative data, California has robust data for childbirth cohorts and accounts for over 12% of US births. 43 The size of the annual birth cohort allows for analysis of rare outcomes over a relatively short period of time.…”
Section: Commentmentioning
confidence: 99%
“…Dural puncture remains the most frequent complication of epidural placement during labor. 3 It may compromise the quality of the postpartum period and lead to liability claims. 4,5 Five risk factors for difficult neuraxial block have been reported in the literature: difficult palpation of bony landmarks, obesity, spinal deformity, inability of the patient to flex his/her back, and operator's low level of experience.…”
mentioning
confidence: 99%